Empowering the Young Generation with Financial Literacy - Abisono, Firya Qurratu'ain; Sri Hastjarjo; Novita Haryono; Aulia Suminar Ayu; Andrine Prima Afneta Arzil; Diah Kusumawati; Pawito; Hamid Arifin (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
Many young people adhere to the principle of YOLO or You Only Live Once, so this is a reason to use personal finances for self-reward or to buy everything they like, especially when they start to have their income. In connection with this situation, Bank Indonesia as the Central Bank has a mission to help increase the financial market deepening to strengthen the effectiveness of Bank Indonesia policies and support national economic financing. Bank Indonesia also wants to create an Indonesian society with a better understanding of financial literacy amidst the increasing enthusiasm of the younger generation to start investing but does not yet have adequate financial investment literacy. From this perspective, our Group Research helps with communication strategy issues related to financial literacy for the younger generation so that the information provided can be disseminated to the right targets and in a way that is easily accepted. Targeting the young generation aged 21-35 years, we held a workshop with the title Financial Literacy: Young, Smart, and Safe in Transactions and Investing as a communication strategy for public literacy to correctly recognize and understand the forms of investment and banking products that suit their character.